STRATEGY FORMULATION DESIGN IN MUALAT NAHDLATUL ULAMA SHARIA COOPERATIVE - Mutqi Sopiawadi; Tigin Lugiani (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2023)
The fisheries sector is a sector that can have an influence on the increase in gross domestic product (GDP). Reporting from kkp.go.id the fisheries sub-sector showed positive growth, rising 9.69% in the second quarter of 2021 even though the co-19 pandemic was still hitting Indonesia. The increase was triggered by increased production of aquaculture and capture fisheries due to favorable weather. The Muamalat Nahdlatul Ulama Cooperative is a small people's economic institution, founded by Nahdhiyin Kasomalang residents who have a desire to work towards productive endeavors in increasing the economic activities of small entrepreneurs based on cooperative and Sharia principles. This research method uses descriptive research methods with a qualitative approach. So, based on the background and the phenomena that exist, the researcher concludes that the right business development being carried out by the Muamalat Dahdlatul Ulama Cooperative is currently developing a business engaged in fish farming through the biofloc system.